Utilizing Large Language Models for Advanced Service Management: Potential Applications and Operational Challenges - Sudhakar Reddy Peddinti; Subba Rao Katragadda; Brij Kishore Pandey; Ajay Tanikonda (Journal of Science & Technology, 2023)
The rapid evolution of large language models (LLMs), exemplified by architectures such as GPT-3, has enabled transformative applications across various industries. In service management, these models demonstrate remarkable potential for enhancing operational efficiency, customer experience, and decision-making processes. This paper examines the deployment of LLMs in advanced service management, focusing on critical applications such as automated customer support, dynamic ticket classification, and real-time knowledge retrieval. By leveraging their ability to process and generate human-like language, LLMs can automate repetitive tasks, augment human operators, and streamline workflows in service ecosystems characterized by high complexity and diverse customer interactions. Automated customer support, powered by LLMs, enables the development of sophisticated conversational agents capable of addressing queries with contextual depth and adaptability, reducing response times and operational costs. Additionally, ticket classification systems employing LLMs demonstrate enhanced accuracy and flexibility in categorizing service requests, ensuring optimal resource allocation and prioritization. Real-time knowledge retrieval, facilitated by LLMs, revolutionizes decision-making processes by extracting actionable insights from vast repositories of organizational data. These applications not only improve service quality but also empower organizations to deliver tailored, context-aware solutions to their clients. Despite these promising advancements, several operational challenges merit careful consideration. Performance concerns, such as hallucinations and inconsistent outputs, can undermine the reliability of LLM-driven systems. Moreover, the computational demands and associated costs of deploying and maintaining LLM infrastructure pose significant barriers to widespread adoption, particularly for small and medium-sized enterprises. Ethical dilemmas, including biases embedded within the models, data privacy issues, and potential misuse, further complicate their integration into service management frameworks. Addressing these challenges necessitates a multidisciplinary approach, encompassing advancements in model training techniques, the adoption of ethical AI principles, and the development of cost-effective solutions tailored to the needs of various industries. The paper underscores the critical importance of robust evaluation metrics to assess the effectiveness and scalability of LLM implementations in service management. Case studies are presented to illustrate the practical implications and measurable outcomes of integrating LLMs into service workflows, highlighting best practices and lessons learned. Furthermore, the discussion identifies future research directions, emphasizing the need for continuous innovation in model optimization, domain-specific fine-tuning, and the development of regulatory frameworks to govern LLM applications responsibly.